Sustaining Thai Government Agency Innovation through Design Thinking Learning Effectiveness - Promsiri, Triyuth; Sukavejworakit, Krisakorn; Keerativutisest, Vasu; Virasa, Thanaphol; Kampanthong, Krischanan (My University, 2022)
Thailand’s 4.0 strategy intends to achieve prosperity, security, and sustainability for its citizens both today and in the distant future. By focusing on the public sector and its civil servants, the government is driving innovation in the public sector by using design thinking (DT) to train government officials to improve public sector innovation (PSI). However, despite studies being conducted on DT and its increasing popularity among scholars, there is still a gap between knowledge and practice with regard to the learning effectiveness of the DT methodology in terms of fostering public sector innovation. Therefore, the authors’ objective for this study was to explore the effectiveness of DT in the Thai PSI and measure the learning effectiveness of the design thinking method (DTM). The researchers conducted action research through a series of workshops and in-class activities involving both qualitative and quantitative approaches. The sample was made up of government officials participating in the Thai Government Innovation Lab (GIL) project in 2020 and 2021. The results on the effectiveness of the program showed that fostering government innovation through DT education led to highly sustainable and highly effective outcomes. This study contributes to the development of public innovation by implementing the DTM as a core methodology for fostering innovation in public organizations.
Keywords: design process; design thinking by GovLab; design thinking method; designerly thinking; Government Innovation Lab; public sector innovation; Thailand